PERBANDINGAN KONSUMSI BAHAN BAKAR ANTARA KARBURATOR VARIABLE VENTURI DENGAN KARBURATOR KECEPATAN KONSTANBERKAPASITAS MESIN 150 CC - abdul khohar; Reinaldi Teguh Setyawan (Program Studi Teknik Mesin dan Otomotif Politeknik Baja Tegal, 2021)
The use of motorcycles is currently experiencing a very rapid increase. This vehicle is usually used for the UMKM sector because it is easy to use and light maintenance.The viar karya 150 tricycle still uses a 4-tak engine, and the carburetor fuel system becomes an injection.Tricycle still use a 4-no engine and carburetor system.In the carburetor there is a system of constant speed work and variable venturi which has a very large effect on engine rotation and fuel consumption according to the type of carburetor.The background, then can be done research the influence of different types of carburetors.Research was conducted on some of the first types of variable venturi carburetor carburetors and constant speeds with engine revs of 3000 rpm (30 km/h) and pertalite fuel.The test is done by measuring and recording the time of fuel consumption, then analyzing the constant speed carburetor and variable venturi.The result of each type of carburetor against fuel consumption is that each mathematical test of variable venturi carburetor (standard) is 10.52 minutes, at a constant speed of 12.35 minutes.So that the replacement of carburetors can reduce fuel consumption by 15.80%. Direct testing with a speed of approximately 25 km / h, namely the venturi variable carburetor 1.42 km and the constant speed carburetor 1.53 km.So that the replacement of carburetors can reduce material consumption by 7.75% without reducing the performance / performance of the vehicle. Keywords: tricycle, fuel, carburetor, 4-stroke motor.